Toughened modified composite plastic particles and a method for their production
Patent Information
- Application Number
- CN202511909452.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-17
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2045-12-17
AI Technical Summary
然而,其固有的脆性,即较差的韧性和抗冲击性能,是制约其在要求更高可靠性和抗损伤能力的结构部件中应用的关键瓶颈
[0033]有益效果是:1、本发明通过制备结构为树枝状的支化聚氨酯多孔颗粒,然后采用模板法,以支化聚氨酯多孔颗粒作为模板,通过真空浸渍使氧化石墨烯-氧化镱分散液中的氧化石墨烯-氧化镱无机复合物附着于支化聚氨酯多孔颗粒表面,然后进行高温炭化去除支化聚氨酯多孔颗粒模板,制得支化氧化石墨烯-氧化镱框架填料,从而复制了支化聚氨酯模板的支化结构,形成互连的三维网络骨架,骨架由氧化石墨烯片层构成主体,分支末端形成纳米级尖端,提供高比表面积,防止团聚,将其与环氧树脂混合后,其有序的支化结构不仅能够诱导裂纹进行偏转,而且环氧树脂与分支紧密接触,其界面在受外力脱粘时能够耗散大量的能量,从而能够大幅增强增韧改性复合塑料粒子的韧性。
Abstract
Description
Technical Field
[0001] This invention belongs to the field of epoxy resin composite material technology, specifically relating to a toughened modified composite plastic particle and its preparation method. Background Technology
[0002] Epoxy resins are widely used in composite materials, electronic packaging, coatings, and adhesives due to their excellent bonding properties, mechanical strength, chemical resistance, and dimensional stability. However, their inherent brittleness, namely poor toughness and impact resistance, is a key bottleneck restricting their application in structural components requiring higher reliability and damage resistance.
[0003] To overcome the poor toughness of epoxy resins, existing technologies often introduce flexible segments or rubber phases into the epoxy network through complex chemical copolymerization reactions, or introduce rigid or flexible nanoparticles through physical blending for toughening. However, while introducing flexible components through chemical modification can improve toughness, it is often accompanied by a significant decrease in material rigidity and heat resistance, and the synthesis process is complex, increasing cost and control difficulty. While directly adding nanoparticles (such as nano-silica, carbon nanotubes, graphene oxide, etc.) for toughening can improve performance to some extent, the toughening effect is often limited by the structure of the nanoparticles themselves. These nanoparticle fillers in the epoxy matrix usually present as isolated and dispersed particles, fibers, or sheet structures. Their simple geometry and spatial arrangement make it difficult to effectively control the crack propagation path, have limited deflection effect on cracks, and fail to form a large energy-dissipating zone in front of the crack tip, resulting in limited improvement in toughening efficiency. Summary of the Invention
[0004] To address the aforementioned technical deficiencies, this invention presents a toughened modified composite plastic particle and its preparation method. The toughened modified composite plastic particle is prepared by adding oleophilic branched graphene oxide-ytterbium oxide framework filler to epoxy resin, exhibiting high toughness and heat resistance.
[0005] A method for preparing toughened modified composite plastic particles includes the following steps:
[0006] S1: Preparation of branched polyurethane porous particles
[0007] Dipentaerythritol was dissolved in N,N-dimethylformamide, hexamethylene diisocyanate was added, and the mixture was heated and stirred. Triethanolamine was then added, stirred until homogeneous, and allowed to stand. Hexamethylene diisocyanate was then added again, and the mixture was heated and stirred to obtain a prepolymer solution. Sorbitol was added, and the mixture was concentrated and precipitated by stirring at high temperature. The filter residue was collected and washed to obtain branched polyurethane. The branched polyurethane was dissolved in dimethyl sulfoxide, frozen, and then placed in deionized water and stirred. After filtration, washing, and drying to constant weight, branched polyurethane porous particles were obtained.
[0008] S2: Template method for preparing branched graphene oxide-ytterbium oxide framework fillers
[0009] Ytterbium nitrate pentahydrate and urea were dissolved in deionized water to prepare a ytterbium nitrate solution. The ytterbium nitrate solution and graphene oxide dispersion were mixed and polyvinylpyrrolidone was added. After ultrasonic dispersion, a hydrothermal reaction was carried out to obtain a graphene oxide-ytterbium oxide dispersion. Then, branched polyurethane porous particles were added and vacuum impregnated. After filtration and drying, composite particles were obtained. Then, high-temperature carbonization was carried out to obtain a branched graphene oxide-ytterbium oxide framework filler.
[0010] S3: Oleophilic modification of branched graphene oxide-ytterbium oxide framework filler
[0011] Deionized water and anhydrous ethanol were placed in a container, and dodecyltrimethoxysilane was added and mixed evenly. Then, glacial acetic acid was added to adjust the pH and allowed to stand to obtain an oleophilic modified solution. The branched graphene oxide-ytterbium oxide framework filler was immersed in the oleophilic modified solution, washed and dried to obtain the oleophilic branched graphene oxide-ytterbium oxide framework filler.
[0012] S4: Preparation of epoxy resin composite plastic particles
[0013] Bisphenol A diglycidyl ether, methyltetrahydrophthalic anhydride and N,N-dimethylbenzylamine were mixed evenly to obtain an epoxy prepolymer. Lipophilic branched graphene oxide-ytterbium oxide framework filler was added to the epoxy prepolymer and stirred evenly. After vacuum degassing, the mixture was placed in a twin-screw extruder for extrusion granulation to obtain composite plastic particles.
[0014] Furthermore, the preparation of branched polyurethane porous particles in step S1 specifically includes the following steps:
[0015] S1.1: Dissolve 1-2 parts of dipentaerythritol in 800-1000 parts of N,N-dimethylformamide, then add 5-5.5 parts of hexamethylene diisocyanate, stir at 80-85℃ for 3-3.5h, then cool to 45-50℃, add 15-17 parts of triethanolamine, stir evenly and let stand for 12-15min, then add 32-35 parts of hexamethylene diisocyanate, stir at 60-65℃ for 1.5-2h, then heat to 80-85℃ and stir for 3.5-4h, then cool to 40-45℃ to obtain a prepolymer solution;
[0016] S1.2: Add 5-6 parts of sorbitol to the prepolymer solution prepared in step S1.1, stir at 70-75℃ for 4-5 hours, then concentrate to 20-25% of the original volume, add 15-20 times the volume of deionized water and stir for 2-2.5 hours, filter and collect the filter residue, wash with methanol 2-3 times, and dry at 80-85℃ to obtain branched polyurethane;
[0017] S1.3: At 80-85℃, 4-6 parts of branched polyurethane are completely dissolved in 60-80 parts of dimethyl sulfoxide, then sealed and frozen, and then placed in 15-20 times the volume of deionized water at 4-5℃ and stirred for 2-3 hours. After filtration and collection of filter residue, the residue is washed 2-3 times with deionized water, and then dried at 80-85℃ to constant weight to obtain branched polyurethane porous particles.
[0018] Further, step S2, the preparation of branched graphene oxide-ytterbium oxide framework filler using the template method, specifically includes the following steps:
[0019] S2.1: Dissolve ytterbium nitrate pentahydrate in deionized water, then add urea and stir until completely dissolved to prepare a ytterbium nitrate solution. Mix the ytterbium nitrate solution with a graphene oxide dispersion with a concentration of 25-30 mg / mL at a volume ratio of 1:(1-1.2) to obtain a mixed solution.
[0020] S2.2: Add 2-3 wt% polyvinylpyrrolidone to the mixed solution, then sonicate at an ultrasonic frequency of 20-25 kHz for 15-20 min, stir at 80-85℃ for 3-5 h, and then place it in a hydrothermal reactor. Heat the reactor to 175-185℃ and react for 15-20 h to obtain a graphene oxide-ytterbium oxide dispersion.
[0021] S2.3: Add 8-10 wt% of branched polyurethane porous particles to the graphene oxide-ytterbium oxide dispersion, then transfer it to a vacuum impregnation tank and impregnate it under vacuum at 400-600 Pa for 15-20 min. Filter the residue and dry it at 90-100℃ for 1.5-2 h to obtain composite particles. Place the composite particles under high temperature carbonization treatment at 750-800℃ for 1-1.5 h to obtain branched graphene oxide-ytterbium oxide framework packing.
[0022] Furthermore, the oleophilic modification of the branched graphene oxide-ytterbium oxide framework filler in step S3 specifically includes the following steps:
[0023] S3.1: Mix deionized water and anhydrous ethanol in a mass ratio of 1:(2.5-3) in a container, then add 2-3wt% dodecyltrimethoxysilane, and stir magnetically for 10-15 minutes at 40-42℃ until homogeneous. Then add glacial acetic acid to adjust the pH to 5.5-6, and let stand for 20-24 hours to obtain a lipophilic modified solution.
[0024] S3.2: The branched graphene oxide-ytterbium oxide framework filler is immersed in an oleophilic modification solution for 8-10 hours, then immersed and washed in anhydrous ethanol solution for 5-10 minutes, and then transferred to an oven at 80-85℃ to dry for 4-5 hours to obtain the oleophilic branched graphene oxide-ytterbium oxide framework filler.
[0025] Furthermore, the preparation of epoxy resin composite plastic particles in step S4 specifically includes the following steps:
[0026] S4.1: Bisphenol A diglycidyl ether, methyltetrahydrophthalic anhydride and N,N-dimethylbenzylamine are mixed uniformly in a mass ratio of 100:(82-85):(1-1.05) to obtain an epoxy prepolymer;
[0027] S4.2: Add oleophilic branched graphene oxide-ytterbium oxide framework filler to the epoxy prepolymer at a mass ratio of 1:(10-12), stir thoroughly at a stirring speed of 600-800 rpm for 15-20 min, then place in a vacuum oven at 85-90℃ for vacuum degassing for 8-10 min, and then place in a twin-screw extruder for extrusion granulation at a working temperature of 120-140℃ and a screw speed of 100-150 rpm to obtain epoxy resin particles, and then heat treat at 150-160℃ for 2-2.5 h to obtain toughened modified composite plastic particles.
[0028] Further, in step S1.3, the branched polyurethane is completely dissolved in dimethyl sulfoxide and then sealed and frozen at a temperature of -25 to -30°C for 2-3 days.
[0029] Furthermore, in step S2.1, the concentration of ytterbium nitrate in the ytterbium nitrate solution is 18-20 mg / mL, and the concentration of urea is 4-6 mg / mL.
[0030] Furthermore, the graphene oxide sheet diameter in the graphene oxide dispersion in step S2.1 is 0.8-1 μm.
[0031] Furthermore, in step S4.1, the epoxy value of bisphenol A diglycidyl ether is 0.5-0.6 mol / 100g.
[0032] A toughened modified composite plastic particle is prepared by the above-mentioned method for preparing toughened modified composite plastic particles.
[0033] The beneficial effects are as follows: 1. This invention prepares branched polyurethane porous particles with a dendritic structure, and then uses a template method, with the branched polyurethane porous particles as templates, to attach the graphene oxide-ytterbium oxide inorganic composite in the graphene oxide-ytterbium oxide dispersion to the surface of the branched polyurethane porous particles through vacuum impregnation. Then, high-temperature carbonization is performed to remove the branched polyurethane porous particle template, thereby obtaining a branched graphene oxide-ytterbium oxide framework filler. This replicates the branched structure of the branched polyurethane template, forming an interconnected three-dimensional network skeleton. The skeleton is mainly composed of graphene oxide sheets, and the branch ends form nanoscale tips, providing a high specific surface area and preventing agglomeration. When mixed with epoxy resin, its ordered branched structure can not only induce crack deflection, but also ensure that the epoxy resin and branches are in close contact. When the interface is debonded by external force, it can dissipate a large amount of energy, thereby significantly enhancing the toughness of the toughened modified composite plastic particles.
[0034] 2. This invention involves preparing a ytterbium nitrate solution and mixing it with a graphene oxide dispersion for a hydrothermal reaction to obtain a graphene oxide-ytterbium oxide dispersion. Then, a branched graphene oxide-ytterbium oxide framework filler is prepared using branched polyurethane porous particles as a template. Ytterbium oxide can effectively inhibit the stacking and slippage of graphene oxide sheets, forcing cracks in the toughened and modified composite plastic particles to bifurcate. At the same time, its high modulus characteristics form local reinforcement points at the branch nodes, hindering the initiation of microcracks. This gives the filler a high energy dissipation capacity when subjected to shear stress, further improving the toughness of the toughened and modified composite plastic particles. Furthermore, the oxygen vacancies on the surface of ytterbium oxide and the oxygen-containing functional groups of graphene oxide bond together with the epoxy molecular chains, which can increase the glass transition temperature of the epoxy resin, thereby improving its thermal stability.
[0035] 3. This invention involves adding dodecyltrimethoxysilane to a mixed solution of deionized water and anhydrous ethanol, then adjusting the pH with glacial acetic acid to obtain an oleophilic modified solution. The branched graphene oxide-ytterbium oxide framework filler is then immersed in the oleophilic modified solution for modification, which enables it to be fully dispersed in epoxy resin and thus better exert its role in toughening epoxy resin. Detailed Implementation
[0036] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0037] Unless otherwise specified, all parts in the following examples refer to parts by weight.
[0038] Example 1
[0039] A method for preparing toughened modified composite plastic particles specifically includes the following steps:
[0040] S1: Preparation of branched polyurethane porous particles
[0041] S1.1: Dissolve 1 part of pentaerythritol in 800 parts of N,N-dimethylformamide, then add 5 parts of hexamethylene diisocyanate, stir at 80°C for 3 hours, then cool to 45°C, add 15 parts of triethanolamine, stir evenly and let stand for 12 minutes, then add 32 parts of hexamethylene diisocyanate, stir at 60°C for 1.5 hours, then heat to 80°C and stir for 3.5 hours, then cool to 40°C to obtain a prepolymer solution;
[0042] S1.2: Add 5 parts of sorbitol to the prepolymer solution prepared in step S1.1, stir at 70°C for 4 hours, then concentrate to 20% of the original volume, add 15 times the volume of deionized water and stir for 2 hours, filter and collect the filter residue, wash twice with methanol, and dry at 80°C to obtain branched polyurethane.
[0043] S1.3: At 80℃, 4 parts of branched polyurethane were completely dissolved in 60 parts of dimethyl sulfoxide, then sealed and frozen at -25℃ for 2 days. The mixture was then placed in 15 times its volume of deionized water at 4℃ and stirred for 2 hours. The filter residue was collected by suction filtration and washed twice with deionized water. The mixture was then dried at 80℃ to constant weight to obtain branched polyurethane porous particles.
[0044] S2: Template method for preparing branched graphene oxide-ytterbium oxide framework fillers
[0045] S2.1: Dissolve ytterbium nitrate pentahydrate in deionized water, then add urea and stir until completely dissolved to prepare a ytterbium nitrate solution with a concentration of 18 mg / mL and a urea concentration of 4 mg / mL. Mix the ytterbium nitrate solution and a graphene oxide dispersion with a concentration of 25 mg / mL at a volume ratio of 1:1. The graphene oxide sheet diameter in the graphene oxide dispersion is 0.8 μm to obtain a mixed solution.
[0046] S2.2: Add 2wt% polyvinylpyrrolidone to the mixed solution, then sonicate at a frequency of 20kHz for 15min, stir at 80℃ for 3h, place in a hydrothermal reactor, heat to 175℃ and react for 15h to obtain graphene oxide-ytterbium oxide dispersion.
[0047] S2.3: Add 8 wt% of branched polyurethane porous particles to the graphene oxide-ytterbium oxide dispersion, then transfer it to a vacuum impregnation tank and impregnate it under vacuum at 400 Pa for 15 min. Filter the residue and dry it at 90 °C for 1.5 h to obtain composite particles. Place the composite particles under high temperature carbonization treatment at 750 °C for 1 h to obtain branched graphene oxide-ytterbium oxide framework packing.
[0048] S3: Oleophilic modification of branched graphene oxide-ytterbium oxide framework filler
[0049] S3.1: Deionized water and anhydrous ethanol are mixed in a mass ratio of 1:2.5 in a container, then 2wt% dodecyltrimethoxysilane is added, and the mixture is stirred magnetically for 10 min at 40℃ until homogeneous. Then glacial acetic acid is added to adjust the pH to 5.5, and the mixture is allowed to stand for 20 h to obtain the lipophilic modified solution.
[0050] S3.2: The branched graphene oxide-ytterbium oxide framework filler was immersed in an oleophilic modification solution for 8 hours, then immersed and washed in anhydrous ethanol solution for 5 minutes, and then transferred to an 80℃ oven to dry for 4 hours to obtain the oleophilic branched graphene oxide-ytterbium oxide framework filler.
[0051] S4: Preparation of epoxy resin composite plastic particles
[0052] S4.1: Bisphenol A diglycidyl ether with an epoxy value of 0.5 mol / 100g, methyltetrahydrophthalic anhydride and N,N-dimethylbenzylamine are mixed evenly in a mass ratio of 100:82:1 to obtain an epoxy prepolymer.
[0053] S4.2: Add oleophilic branched graphene oxide-ytterbium oxide framework filler to the epoxy prepolymer at a mass ratio of 1:10, mix thoroughly at a stirring speed of 600 rpm for 15 min, then place in a vacuum oven at 85℃ for vacuum degassing for 8 min, and then place in a twin-screw extruder for extrusion granulation at a working temperature of 120℃ and a screw speed of 100 rpm to obtain epoxy resin particles, and then heat treat at 150℃ for 2 h to obtain toughened modified composite plastic particles.
[0054] Example 2
[0055] A method for preparing toughened modified composite plastic particles specifically includes the following steps:
[0056] S1: Preparation of branched polyurethane porous particles
[0057] S1.1: Dissolve 1.5 parts of dipentaerythritol in 900 parts of N,N-dimethylformamide, then add 5.3 parts of hexamethylene diisocyanate, stir at 85°C for 3.2 h, then cool to 47°C, add 16 parts of triethanolamine, stir evenly and let stand for 15 min, then add 34 parts of hexamethylene diisocyanate, stir at 60°C for 1.8 h, then heat to 85°C and stir for 4 h, then cool to 43°C to obtain a prepolymer solution;
[0058] S1.2: Add 5.5 parts of sorbitol to the prepolymer solution prepared in step S1.1, stir at 72℃ for 4.5h, then concentrate to 22% of the original volume, add 18 times the volume of deionized water and stir for 2.5h, filter and collect the filter residue, wash with methanol 3 times, and dry at 82.5℃ to obtain branched polyurethane.
[0059] S1.3: At 82.5℃, 5 parts of branched polyurethane were completely dissolved in 70 parts of dimethyl sulfoxide, then sealed and frozen at -27.5℃ for 3 days. The mixture was then placed in 18 times its volume of deionized water at 5℃ and stirred for 3 hours. The filter residue was collected by suction filtration and washed 3 times with deionized water. Finally, it was dried at 85℃ to constant weight to obtain branched polyurethane porous particles.
[0060] S2: Template method for preparing branched graphene oxide-ytterbium oxide framework fillers
[0061] S2.1: Dissolve ytterbium nitrate pentahydrate in deionized water, then add urea and stir until completely dissolved to prepare a ytterbium nitrate solution with a concentration of 19 mg / mL and a urea concentration of 5 mg / mL. Mix the ytterbium nitrate solution and a graphene oxide dispersion with a concentration of 28 mg / mL at a volume ratio of 1:1.1. The graphene oxide sheet diameter in the graphene oxide dispersion is 0.9 μm to obtain a mixed solution.
[0062] S2.2: Add 2.5wt% polyvinylpyrrolidone to the mixed solution, then sonicate at a frequency of 23kHz for 18min, stir at 85℃ for 4h, place in a hydrothermal reactor, heat to 185℃ and react for 18h to obtain graphene oxide-ytterbium oxide dispersion.
[0063] S2.3: Add 9 wt% of branched polyurethane porous particles to the graphene oxide-ytterbium oxide dispersion, then transfer it to a vacuum impregnation tank and impregnate it under vacuum at 500 Pa for 18 min. Filter the residue and dry it at 95 °C for 1.8 h to obtain composite particles. Place the composite particles under high temperature carbonization treatment at 775 °C for 1.2 h to obtain branched graphene oxide-ytterbium oxide framework packing.
[0064] S3: Oleophilic modification of branched graphene oxide-ytterbium oxide framework filler
[0065] S3.1: Deionized water and anhydrous ethanol were mixed in a container at a mass ratio of 1:2.8, and then 2.5 wt% dodecyltrimethoxysilane was added. The mixture was stirred magnetically for 13 min at 42 °C until homogeneous. Then, glacial acetic acid was added to adjust the pH to 6, and the mixture was allowed to stand for 22 h to obtain the lipophilic modified solution.
[0066] S3.2: The branched graphene oxide-ytterbium oxide framework filler was immersed in an oleophilic modification solution for 9 hours, then immersed and washed in anhydrous ethanol solution for 8 minutes, and then transferred to an oven at 82.5℃ to dry for 4.5 hours to obtain the oleophilic branched graphene oxide-ytterbium oxide framework filler.
[0067] S4: Preparation of epoxy resin composite plastic particles
[0068] S4.1: Bisphenol A diglycidyl ether, methyltetrahydrophthalic anhydride and N,N-dimethylbenzylamine with an epoxy value of 0.55 mol / 100g are mixed evenly in a mass ratio of 100:83:1.03 to obtain an epoxy prepolymer;
[0069] S4.2: Add oleophilic branched graphene oxide-ytterbium oxide framework filler to the epoxy prepolymer at a mass ratio of 1:11, mix thoroughly at a stirring speed of 700 rpm for 20 min, then place in a vacuum oven at 90℃ for vacuum degassing for 9 min, and then place in a twin-screw extruder for extrusion granulation at a working temperature of 130℃ and a screw speed of 125 rpm to obtain epoxy resin particles, and then heat treat at 155℃ for 2.5 h to obtain toughened modified composite plastic particles.
[0070] Example 3
[0071] A method for preparing toughened modified composite plastic particles specifically includes the following steps:
[0072] S1: Preparation of branched polyurethane porous particles
[0073] S1.1: Dissolve 2 parts of dipentaerythritol in 1000 parts of N,N-dimethylformamide, then add 5.5 parts of hexamethylene diisocyanate, stir at 85°C for 3.5 h, then cool to 50°C, add 17 parts of triethanolamine, stir evenly and let stand for 15 min, then add 35 parts of hexamethylene diisocyanate, stir at 65°C for 2 h, then heat to 85°C and stir for 4 h, then cool to 45°C to obtain a prepolymer solution;
[0074] S1.2: Add 6 parts of sorbitol to the prepolymer solution prepared in step S1.1, stir at 75°C for 5 hours, then concentrate to 25% of the original volume, add 20 times the volume of deionized water and stir for 2.5 hours, filter and collect the filter residue, wash with methanol 3 times, and dry at 85°C to obtain branched polyurethane.
[0075] S1.3: At 85℃, 6 parts of branched polyurethane were completely dissolved in 80 parts of dimethyl sulfoxide, then sealed and frozen at -30℃ for 3 days. The mixture was then placed in 20 times its volume of deionized water at 5℃ and stirred for 3 hours. The filter residue was collected by suction filtration and washed 3 times with deionized water. Finally, it was dried at 85℃ to constant weight to obtain branched polyurethane porous particles.
[0076] S2: Template method for preparing branched graphene oxide-ytterbium oxide framework fillers
[0077] S2.1: Dissolve ytterbium nitrate pentahydrate in deionized water, then add urea and stir until completely dissolved to prepare a ytterbium nitrate solution with a concentration of 20 mg / mL and a urea concentration of 6 mg / mL. Mix the ytterbium nitrate solution and a graphene oxide dispersion with a concentration of 30 mg / mL at a volume ratio of 1:1.2. The graphene oxide sheet diameter in the graphene oxide dispersion is 1 μm to obtain a mixed solution.
[0078] S2.2: Add 3 wt% polyvinylpyrrolidone to the mixed solution, then sonicate at a frequency of 25 kHz for 20 min, stir at 85 °C for 5 h, place in a hydrothermal reactor, heat to 185 °C and react for 20 h to obtain graphene oxide-ytterbium oxide dispersion.
[0079] S2.3: Add 10wt% of branched polyurethane porous particles to the graphene oxide-ytterbium oxide dispersion, then transfer it to a vacuum impregnation tank and impregnate it under vacuum at 600 Pa for 20 min. Filter the residue and dry it at 100℃ for 2 h to obtain composite particles. Place the composite particles under high temperature carbonization treatment at 800℃ for 1.5 h to obtain branched graphene oxide-ytterbium oxide framework packing.
[0080] S3: Oleophilic modification of branched graphene oxide-ytterbium oxide framework filler
[0081] S3.1: Deionized water and anhydrous ethanol are mixed in a 1:3 mass ratio in a container, then 3 wt% dodecyltrimethoxysilane is added, and the mixture is stirred magnetically for 15 min at 42°C until homogeneous. Then glacial acetic acid is added to adjust the pH to 6, and the mixture is allowed to stand for 24 h to obtain the lipophilic modified solution.
[0082] S3.2: The branched graphene oxide-ytterbium oxide framework filler was immersed in an oleophilic modification solution for 10 h, then immersed and washed in anhydrous ethanol solution for 10 min, and then transferred to an 85℃ oven to dry for 5 h to obtain the oleophilic branched graphene oxide-ytterbium oxide framework filler.
[0083] S4: Preparation of epoxy resin composite plastic particles
[0084] S4.1: Bisphenol A diglycidyl ether with an epoxy value of 0.6 mol / 100g, methyltetrahydrophthalic anhydride and N,N-dimethylbenzylamine are mixed evenly in a mass ratio of 100:85:1.05 to obtain an epoxy prepolymer;
[0085] S4.2: Add oleophilic branched graphene oxide-ytterbium oxide framework filler to the epoxy prepolymer at a mass ratio of 1:12, stir thoroughly at a stirring speed of 800 rpm for 20 min, then place in a vacuum oven at 90℃ for vacuum degassing for 10 min, and then place in a twin-screw extruder for extrusion granulation at a working temperature of 140℃ and a screw speed of 150 rpm to obtain epoxy resin particles, and then heat treat at 160℃ for 2.5 h to obtain toughened modified composite plastic particles.
[0086] Comparative Example 1: The difference from Example 1 is that steps S1 and S2.3 were removed in Comparative Example 1. The graphene oxide-ytterbium oxide dispersion obtained in step S2.2 was concentrated and then freeze-dried to obtain a graphene oxide-ytterbium oxide composite material. The branched graphene oxide-ytterbium oxide framework filler in step S3.2 was replaced with a graphene oxide-ytterbium oxide composite material to obtain an oleophilic graphene oxide-ytterbium oxide composite material. The oleophilic branched graphene oxide-ytterbium oxide framework filler in step S4.2 was replaced with an equal mass of oleophilic graphene oxide-ytterbium oxide composite material. All other specific implementation methods are the same as in Example 1.
[0087] Comparative Example 2: The difference from Example 1 is that steps S2.1 and S2.2 are removed in Comparative Example 2. The graphene oxide-ytterbium oxide dispersion in step S2.3 is replaced with a graphene oxide dispersion of equal mass concentration to obtain a branched graphene oxide framework packing. The branched graphene oxide-ytterbium oxide framework packing in step S3.2 is replaced with a branched graphene oxide framework packing to obtain an oleophilic branched graphene oxide framework packing. The oleophilic branched graphene oxide-ytterbium oxide framework packing in step S4.2 is replaced with an equal mass of oleophilic branched graphene oxide framework packing. All other specific implementation methods are the same as in Example 1.
[0088] Comparative Example 3: The difference from Example 1 is that step S3 is removed in Comparative Example 3, and the oleophilic branched graphene oxide-ytterbium oxide framework filler in step S4.2 is replaced with an equal mass of branched graphene oxide-ytterbium oxide framework filler. All other specific implementation methods are the same as in Example 1.
[0089] Test samples were prepared using the composite plastic particles prepared in Examples 1-3 and Comparative Examples 1-3.
[0090] Bending strength: The test samples were adjusted according to the standard GB / T9341-2008, and their bending strength was determined. At least five tests were conducted for each material to determine its average bending strength.
[0091] Fracture toughness: The test samples were adjusted according to the standard GB / T1040.1-2018, and then their fracture toughness was tested. At least five tests were performed on each material to determine its average fracture toughness value. The data were recorded as shown in Table 1.
[0092] Table 1: Performance of Composite Plastic Particle Test Samples
[0093] Bending strength (MPa) <![CDATA[Fracture toughness (MN / m 3 / 2 )]]> Example 1 150.37 2.38 Example 2 151.25 2.48 Example 3 150.62 2.43 Comparative Example 1 121.34 1.81 Comparative Example 2 132.13 1.97 Comparative Example 3 138.96 2.08
[0094] As can be seen from the data in Examples 1-3 in Table 1, the test samples prepared by the toughened modified composite plastic particles prepared in this application have good flexural strength and fracture toughness. As can be seen from the data in Comparative Example 1, the ability of the branched graphene oxide-ytterbium oxide framework filler to toughen epoxy resin is greatly reduced when the branched polyurethane porous particles are not used as a template. This proves that the preparation of branched graphene oxide-ytterbium oxide framework filler to replicate the branched structure of the branched polyurethane template can greatly enhance the toughness of the toughened modified composite plastic particles.
[0095] As can be seen from the data of Comparative Example 2, the toughening effect of the lipophilic branched graphene oxide framework filler prepared without the use of ytterbium oxide and graphene oxide composite is significantly less than that of the lipophilic branched graphene oxide-ytterbium oxide framework filler prepared in Example 1. This proves that the combination of ytterbium oxide and graphene oxide can further improve the toughness of the toughened modified composite plastic particles.
[0096] As can be seen from the data of Example 1 and Comparative Example 3, the preparation of a lipophilic modification solution mainly composed of dodecyltrimethoxysilane to modify the branched graphene oxide-ytterbium oxide framework filler can further improve the toughness of epoxy resin and improve the dispersibility of the filler in epoxy resin.
[0097] Differential scanning calorimetry was performed on the composite plastic particles prepared in Examples 1-3 and Comparative Example 2 to test their glass transition temperature. The heating rate was set to 5°C per minute, and the test temperature range was increased from room temperature to 180°C. The test was conducted in a nitrogen atmosphere. Three samples were taken for each test, and the data were recorded as shown in Table 2.
[0098] Table 2: Glass transition temperatures of composite plastic particles
[0099] Glass transition temperature of sample 1 (°C) Glass transition temperature of sample 2 (°C) Glass transition temperature of sample 3 (°C) Example 1 162.1 163.2 161.8 Example 2 163.7 163.5 164.1 Example 3 165.7 164.8 165.2 Comparative Example 2 138.5 139.4 138.2
[0100] As can be seen from the data in Table 2 of Examples 1-3, the composite plastic particles prepared in this application have a high glass transition temperature, while the glass transition temperature of the composite plastic particles prepared in Comparative Example 2 is significantly lower than that of Examples 1-3. This proves that the composite of ytterbium oxide and graphene oxide can improve the thermal stability of epoxy resin.
[0101] The above embodiments are merely illustrative of the principles and effects of the present invention and are not intended to limit the invention. Any person skilled in the art can modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by those skilled in the art without departing from the spirit and technical concept disclosed in the present invention should still be covered by the claims of the present invention.
Claims
1. A method for preparing toughened modified composite plastic particles, characterized in that, Includes the following steps: S1: Preparation of branched polyurethane porous particles Dipentaerythritol was dissolved in N,N-dimethylformamide, hexamethylene diisocyanate was added, and the mixture was heated and stirred. Triethanolamine was then added, stirred until homogeneous, and allowed to stand. Hexamethylene diisocyanate was then added again, and the mixture was heated and stirred to obtain a prepolymer solution. Sorbitol was added, and the mixture was concentrated and precipitated by stirring at high temperature. The filter residue was collected and washed to obtain branched polyurethane. The branched polyurethane was dissolved in dimethyl sulfoxide, frozen, and then placed in deionized water and stirred. After filtration, washing, and drying to constant weight, branched polyurethane porous particles were obtained. S2: Template method for preparing branched graphene oxide-ytterbium oxide framework fillers Ytterbium nitrate pentahydrate and urea were dissolved in deionized water to prepare a ytterbium nitrate solution. The ytterbium nitrate solution and graphene oxide dispersion were mixed and polyvinylpyrrolidone was added. After ultrasonic dispersion, a hydrothermal reaction was carried out to obtain a graphene oxide-ytterbium oxide dispersion. Then, branched polyurethane porous particles were added and vacuum impregnated. After filtration and drying, composite particles were obtained. Then, high-temperature carbonization was carried out to obtain a branched graphene oxide-ytterbium oxide framework filler. S3: Oleophilic modification of branched graphene oxide-ytterbium oxide framework filler Deionized water and anhydrous ethanol were placed in a container, and dodecyltrimethoxysilane was added and mixed evenly. Then, glacial acetic acid was added to adjust the pH and allowed to stand to obtain an oleophilic modified solution. The branched graphene oxide-ytterbium oxide framework filler was immersed in the oleophilic modified solution, washed and dried to obtain the oleophilic branched graphene oxide-ytterbium oxide framework filler. S4: Preparation of epoxy resin composite plastic particles Bisphenol A diglycidyl ether, methyltetrahydrophthalic anhydride and N,N-dimethylbenzylamine were mixed evenly to obtain an epoxy prepolymer. Lipophilic branched graphene oxide-ytterbium oxide framework filler was added to the epoxy prepolymer and stirred evenly. After vacuum degassing, the mixture was placed in a twin-screw extruder for extrusion granulation to obtain composite plastic particles.
2. The method for preparing toughened modified composite plastic particles according to claim 1, characterized in that, Step S1, the preparation of branched polyurethane porous particles, specifically includes the following steps: S1.1: Dissolve 1-2 parts of dipentaerythritol in 800-1000 parts of N,N-dimethylformamide, then add 5-5.5 parts of hexamethylene diisocyanate, stir at 80-85℃ for 3-3.5h, then cool to 45-50℃, add 15-17 parts of triethanolamine, stir evenly and let stand for 12-15min, then add 32-35 parts of hexamethylene diisocyanate, stir at 60-65℃ for 1.5-2h, then heat to 80-85℃ and stir for 3.5-4h, then cool to 40-45℃ to obtain a prepolymer solution; S1.2: Add 5-6 parts of sorbitol to the prepolymer solution prepared in step S1.1, stir at 70-75℃ for 4-5 hours, then concentrate to 20-25% of the original volume, add 15-20 times the volume of deionized water and stir for 2-2.5 hours, filter and collect the filter residue, wash with methanol 2-3 times, and dry at 80-85℃ to obtain branched polyurethane; S1.3: At 80-85℃, 4-6 parts of branched polyurethane are completely dissolved in 60-80 parts of dimethyl sulfoxide, then sealed and frozen, and then placed in 15-20 times the volume of deionized water at 4-5℃ and stirred for 2-3 hours. After filtration and collection of filter residue, the residue is washed 2-3 times with deionized water, and then dried at 80-85℃ to constant weight to obtain branched polyurethane porous particles.
3. The method for preparing toughened modified composite plastic particles according to claim 2, characterized in that, Step S2, the template method for preparing branched graphene oxide-ytterbium oxide framework fillers, specifically includes the following steps: S2.1: Dissolve ytterbium nitrate pentahydrate in deionized water, then add urea and stir until completely dissolved to prepare a ytterbium nitrate solution. Mix the ytterbium nitrate solution with a graphene oxide dispersion with a concentration of 25-30 mg / mL at a volume ratio of 1:(1-1.2) to obtain a mixed solution. S2.2: Add 2-3 wt% polyvinylpyrrolidone to the mixed solution, then sonicate at an ultrasonic frequency of 20-25 kHz for 15-20 min, stir at 80-85℃ for 3-5 h, and then place it in a hydrothermal reactor. Heat the reactor to 175-185℃ and react for 15-20 h to obtain a graphene oxide-ytterbium oxide dispersion. S2.3: Add 8-10 wt% of branched polyurethane porous particles to the graphene oxide-ytterbium oxide dispersion, then transfer it to a vacuum impregnation tank and impregnate it under vacuum at 400-600 Pa for 15-20 min. Filter the residue and dry it at 90-100℃ for 1.5-2 h to obtain composite particles. Place the composite particles under high temperature carbonization treatment at 750-800℃ for 1-1.5 h to obtain branched graphene oxide-ytterbium oxide framework packing.
4. The method for preparing toughened modified composite plastic particles according to claim 3, characterized in that, Step S3, the oleophilic modification of branched graphene oxide-ytterbium oxide framework filler, specifically includes the following steps: S3.1: Mix deionized water and anhydrous ethanol in a mass ratio of 1:(2.5-3) in a container, then add 2-3wt% dodecyltrimethoxysilane, and stir magnetically for 10-15 minutes at 40-42℃ until homogeneous. Then add glacial acetic acid to adjust the pH to 5.5-6, and let stand for 20-24 hours to obtain a lipophilic modified solution. S3.2: The branched graphene oxide-ytterbium oxide framework filler is immersed in an oleophilic modification solution for 8-10 hours, then immersed and washed in anhydrous ethanol solution for 5-10 minutes, and then transferred to an oven at 80-85℃ to dry for 4-5 hours to obtain the oleophilic branched graphene oxide-ytterbium oxide framework filler.
5. The method for preparing toughened modified composite plastic particles according to claim 4, characterized in that, Step S4, the preparation of epoxy resin composite plastic particles, specifically includes the following steps: S4.1: Bisphenol A diglycidyl ether, methyltetrahydrophthalic anhydride and N,N-dimethylbenzylamine are mixed uniformly in a mass ratio of 100:(82-85):(1-1.05) to obtain an epoxy prepolymer; S4.2: Add oleophilic branched graphene oxide-ytterbium oxide framework filler to the epoxy prepolymer at a mass ratio of 1:(10-12), stir thoroughly at a stirring speed of 600-800 rpm for 15-20 min, then place in a vacuum oven at 85-90℃ for vacuum degassing for 8-10 min, and then place in a twin-screw extruder for extrusion granulation at a working temperature of 120-140℃ and a screw speed of 100-150 rpm to obtain epoxy resin particles, and then heat treat at 150-160℃ for 2-2.5 h to obtain toughened modified composite plastic particles.
6. The method for preparing toughened modified composite plastic particles according to claim 2, characterized in that, In step S1.3, the branched polyurethane is completely dissolved in dimethyl sulfoxide and then sealed and frozen at a temperature of -25 to -30°C for 2-3 days.
7. The method for preparing toughened modified composite plastic particles according to claim 3, characterized in that, In step S2.1, the concentration of ytterbium nitrate in the ytterbium nitrate solution is 18-20 mg / mL, and the concentration of urea is 4-6 mg / mL.
8. The method for preparing toughened modified composite plastic particles according to claim 3, characterized in that, In step S2.1, the graphene oxide flakes in the graphene oxide dispersion have a diameter of 0.8-1 μm.
9. The method for preparing toughened modified composite plastic particles according to claim 5, characterized in that, In step S4.1, the epoxy value of bisphenol A diglycidyl ether is 0.5-0.6 mol / 100g.
10. A toughened modified composite plastic particle, characterized in that, It is prepared by the method for preparing toughened modified composite plastic particles according to any one of claims 1-9.
Citation Information
Patent Citations
Preparation process of graphene nanocomposite material
CN111763406A
Nano-modified high-strength high-elasticity modulus polyurethane epoxy resin for reinforced carbon fiber composite transmission tower and preparation method thereof
CN113999486A